When doing good will not save us: revisiting the buffering effect of CSR following service failures - Antonetti, Paolo; Crisafulli, Benedetta; Maklan, Stan (Wiley, 2021)
Past research offers inconsistent evidence on whether CSR is an effective service recovery strategy. Current debates overlook the signals that service failures send about the company, and their interplay with CSR. We propose a moderated mediation model showing that CSR's effectiveness for service recovery depends upon failure type. For failures signaling a lack of skills and expertise, CSR enhances warmth which in turn lowers revenge. Warmth further increases perceived competence which influences conciliatory responses. CSR, however, does not help if the failure signals a lack of moral integrity. Both warmth and competence explain the CSR's buffering effect. Our study demonstrates that “doing good” helps only to the extent that service failures that do not raise doubts about the character of the company. Even in these circumstances, however, the buffering effect of CSR is observed only in case of customer–firm communal relationships. Consistent evidence from three experiments revisits more optimistic assessments of the ability of CSR to act as a recovery strategy and shows that CSR can help only under very circumscribed conditions. Managerially, we show how and when the CSR buffer applies in service contexts, offering insights on how managers can best reap the potential benefits of service brands' involvement in CSR.
Keywords: buffering effect; competence; corporate social responsibility; service recovery,; warmth